2001
DOI: 10.1111/j.1740-8261.2001.tb00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Appearance of an Equine Testicular Seminoma

Abstract: A 16-year-old thoroughbred stallion developed sudden swelling of the left testicle. The stallion had previously been regarded as a unilateral cryptorchid. Ultrasound examination of the left testicle revealed a diffusely heterogeneous parenchyma. The testicle was diffusely hypoechoic with ill defined regions of hyperechogenicity giving the appearance of hypoechoic nodules throughout the testicular parenchyma. No normal testicular tissue was identifiable. An echogenic band, representing a pseudocapsule could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 7 publications
3
20
0
Order By: Relevance
“…The testicle appears diffusely hypoechoic with ill-defined regions of hyperechogenicity giving the appearance of hypoechoic nodules throughout the parenchyma. Anechogenic band, representing a pseudocapsule, could be seen surrounding the testicle [3]. In cases of malignant mixed sex cord-stromal tumour, ultrasonographic evaluation of the testes revealed diffuse heterogeneous parenchyma with multiple hypoechoic nodular areas [5,22].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The testicle appears diffusely hypoechoic with ill-defined regions of hyperechogenicity giving the appearance of hypoechoic nodules throughout the parenchyma. Anechogenic band, representing a pseudocapsule, could be seen surrounding the testicle [3]. In cases of malignant mixed sex cord-stromal tumour, ultrasonographic evaluation of the testes revealed diffuse heterogeneous parenchyma with multiple hypoechoic nodular areas [5,22].…”
Section: Discussionmentioning
confidence: 94%
“…However, to our knowledge, scant information is available on the ultrasonographic appearance of different testicular tumours in the stallion [3,5,22] and imaging findings of intra-abdominal mature teratomas in undescended testis have been very rarely reported in the horse [8].…”
Section: Introductionmentioning
confidence: 99%
“…Echodense flocculent material within an encapsulated mass has not been described in published reports of testicular tumours. Seminomas are reported to have a hypoechoic, homogeneous appearance with sharply demarcated borders (Beck et al 2001), whereas teratomas are reported to be heterogeneous with cystic spaces, often containing areas of acoustic shadowing and generally having poorly defined margins (Brinsko 1998;Tnibar et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Testicular neoplasia can be of germinal or nongerminal origin (Brinsko 1998). Primary testicular/paratesticular neoplasms of horses include interstitial (Leydig) cell tumours (Gelberg and McEntee 1987;May et al 1999;Melo et al 2007), seminomas (Hunt et al 1990;Beck et al 2001;Threlfall et al 2005;Christensen et al 2007), Sertoli (sustentacular) cell tumours (Pratt et al 2003;Threlfall et al 2005), teratomas (Pollock et al 2002), teratocarcinomas (Shaw and Roth 1986), embryonal carcinomas (Valentine and Weinstock 1986), leiomyomas (Klug et al 1972;Johnson and Steinberg 1989), leiomyosarcomas (Allison and Moeller 1999) and mixed, germ cell-sex cord-stromal neoplasms (Cullen et al 1987).…”
Section: Introductionmentioning
confidence: 99%